A more general exergy function and its application to the definition of exergy efficiency. (1st July 2015) - Zanchini, Enzo
Abstract: An availability function which includes the usual functions exergy and flow exergy as special cases is defined and called exergy. The new definition of exergy is based on the concept of pressure energy, namely the work that must be done on a stationary external pressure field to build inside it the region of space occupied by the system. Then, the definition of exergy efficiency is written in a more explicit form, where the same availability function is employed for both steady-flow processes and non-flow processes. Highlights: An availability function more general than the usual ones is defined and called exergy. The new exergy function applies both to non-flow and to steady-flow processes. The new function is used to state a more explicit definition of exergy efficiency.